Efektivitas Pelayanan Pembayaran Non Tunai Pada Tempat Pemungutan Retribusi Pariwisata Di Kabupaten Gunungkidul - Suhartapa; Linda Kurniawati; Amin Kiswantoro (STIE Pariwisata API Yogyakarta, 2025)
Natural beach tourism is still a favorite for most tourists visiting Gunungkidul Regency. There are dozens of levy collection points managed by the Yogyakarta Special Region Gunungkidul Tourism Office, but only a few provide non-cash levy payment services. This research aims to see the level of effectiveness of levy collection services from the perspective of managers and tourists. Data collection techniques use interviews, observation and documentation. The research method used is a qualitative research method and data analysis techniques in the form of SWOT analysis. The research results show that the implementation of non-cash tourism levy payment services, especially QRIS, has been quite effective in terms of both agencies and tourists. However, several improvements are still needed, including strengthening the internet network and providing widespread outreach to tourists regarding prioritizing non-cash transactions.